Transporte de suprimentos na construção civil: Uma análise do impacto da logística de suprimentos no cronograma físico-financeiro de uma construção modular no Estado do Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
This study examines the geographical reality of the state of Amapá and its influence on supply logistics for construction projects in the region. The focus is on the effects of extended delivery times on the physical-financial schedule of a modular work in Amapá. The research quantifies this impact by using financial performance indicators to compare three distinct scenarios, each simulating different delivery times for the project’s main inputs. This, in turn, alters the disbursement schedule necessary for project execution. The financial indicators used include Net Present Value (NPV), Internal Rate of Return (IRR), and payback period. These indicators helped identify situations where the project had higher financial viability and, consequently, the implications of extended input delivery logistics. The results showed that the scenario with the shortest delivery times resulted in the best financial performance indices. This highlights the significant consequences that logistics and delivery times can have on the financial viability of a construction project in Amapá.
Keywords: Logística de suprimentos; Logística de suprimentos; Infraestrutura regional - Amapá (AP); CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ODS 9 – Indústria, inovação e infraestrutura; ODS 11 – Cidades e comunidades sustentáveis; ODS 12 – Consumo e produção responsáveis